SPORTS CULTURAL MEETING PLAYFUL (ELEC) (Fiep Bulletin - online, 2013)
The work presented is the result of a project called "ELEC-Cultural Encounter Playful Sports" Pedagogical Faveira developed in Unity, Isle of Cotijuba, Insular region of Belém-Pará, in the months of April, June and September of that year, which is goal oportunizar access to students aged 04 to 16 years to participate in some sporting various movements, integrating learning with leisure, promoting education through movements so playful and pleasurable sport, a proposal of fun inside and out educational institution in which each student can educate themselves playing. We start with the assertion Assis de Oliveira, 2001, p.20 that "indoor games, represented by the sport, still, even if unconsciously, a reaffirmation of codes, values ??and fundamental meanings of capitalist society" thereby sports and cultural activities has an important function in the life of a student who comes to be seen as a social, historical and cultural. However, the student is not just a figment of their socio cultural context, but the author of his own story, he is a producer and be completely adjusted to their knowledge, in the act of interacting with each other in games, games and sports activities that address the characteristics of people Paraense, specifically those living in regions in which ribeinhas requires movement, coordination and balance. The methodology consisted of driving through language-body gestural, linked with the emerging languages??, cultural, and plastic body-gestural-visual. The learning situations strengthened several languages ??requiring socialization and interaction among students and contributed to new discoveries and creations on culture and movements acquired and rebuilt by educating for healthy growth and ensuring a promising future.
Keywords: education; recreation; learning